Analisis Yuridis Perjanjian Kawin Dalam Perkawinan Campuran : Studi Penetapan No. 599/Pdt.P/2017/PN.Mlg - Ramona Milenia Rohadi; M. Yazid Fathoni (Private Law, 2022)
This study aims to analyze the basis of the judge's legal considerations associated with the determination of the Malang District Court Number 599/Pdt.P/2017/PN.Mlg and the making a marriage agreement according to Law no. 1 of 1974 concerning Marriage and the Constitutional Court Decision No. 69/PUU-XIII/2015. This type of research is normative research with a statutory approach (Statue Approach), a conceptual approach (Conceptual Approach), and a case approach (Case Approach) and uses qualitative analysis. The results of this study, the basis of the judge's legal considerations in Decision Number 599/Pdt.P/2017/PN.Mlg is due to the marriage agreement deed made before a Notary based on the Constitutional Court Decision Number 69/PUU /XIII/2015, that the marriage agreement can be made after the marriage performed. While the time of making the marriage agreement based on the Constitutional Court Decision No. 69/PUU-XIII/2015 stipulates that the marriage agreement can be made before it is held or during the marriage bond can and ratified by the Marriage Registrar or Notary.